Visualizing an Ultra‐Weak Protein–Protein Interaction in Phosphorylation Signaling1. Issue 43 (11th August 2014) - Xing, Qiong; Huang, Peng; Yang, Ju; Sun, Jian‐Qiang; Gong, Zhou; Dong, Xu; Guo, Da‐Chuan; Chen, Shao‐Min; Yang, Yu‐Hong; Wang, Yan; Yang, Ming‐Hui; Yi, Ming; et al.
Abstract Proteins interact with each other to fulfill their functions. The importance of weak protein–protein interactions has been increasingly recognized. However, owing to technical difficulties, ultra‐weak interactions remain to be characterized. Phosphorylation can take place via a KD≈25 mM interaction between two bacterial enzymes. Using paramagnetic NMR spectroscopy and with the introduction of a novel GdIII‐based probe, we determined the structure of the resulting complex to atomic resolution. The structure accounts for the mechanism of phosphoryl transfer between the two enzymes and demonstrates the physical basis for their ultra‐weak interaction. Further, molecular dynamics (MD) simulations suggest that the complex has a lifetime in the micro‐ to millisecond regimen. Hence such interaction is termed a fleeting interaction. From mathematical modeling, we propose that an ultra‐weak fleeting interaction enables rapid flux of phosphoryl signal, providing a high effective protein concentration.